2010
DOI: 10.5194/tc-4-359-2010
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of glacier advance over deforming till

Abstract: Abstract. The advance of a glacier over a deforming sediment layer is analysed numerically. We treat this problem as a contact problem involving two slowly-deforming viscous bodies. The surface evolution of the two bodies, and of the contact interface between them, is followed through time. Using various different non-linear till rheologies, we show how the mode of advance depends on the relative effective viscosities of ice and till. Three modes of advances are observed: (1) overriding, where the glacier adva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The till was modelled as viscous medium using a flow law of the same form as GlenSteinemann constitutive law. This approach of introducing basal motion has been used in numerous numerical studies, and a recent example for this approach with detailed description can be found in Leysinger Vieli and Gudmundsson (2010).…”
Section: Basal Boundary Conditionmentioning
confidence: 99%
“…The till was modelled as viscous medium using a flow law of the same form as GlenSteinemann constitutive law. This approach of introducing basal motion has been used in numerous numerical studies, and a recent example for this approach with detailed description can be found in Leysinger Vieli and Gudmundsson (2010).…”
Section: Basal Boundary Conditionmentioning
confidence: 99%
“…Stimulated by Haeberli, expertise was combined between the disciplines of geotechnics (Arenson 2002), geophysics (Musil 2002; Maurer et al . 2010) and glaciology (Leysinger Vieli 2003) to investigate the Muragl rock glacier in the Engadine in the Swiss Alps (Fig. 1) as the first of two ETH‐funded multi‐investigator projects to promote better process understanding, to lead to more effective future modelling and prediction of behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The 2000s in Svalbard were likely warmer than any period in the previous 1000 yr (Grinsted et al, 2006;Virkkunen et al, 2007;Divine et al, 2011). Dunse et al (2009) identify a high amount of surface melt over the southern part of ASF in summer 2004, followed by lowering of the firn line and increase in SMB until 2007 (see also Moholdt et al (2010)).…”
Section: Discussionmentioning
confidence: 97%